Embalming – History to its Recent Advancements - Shrestha, Sunil (Europasian Journal of Medical Sciences, 2019)
Embalming as art and science of preserving dead bodies with postponing decomposition using embalming fluid. The method of preservation of cadavers is natural and non-natural. This study involves an extensive search of journal articles to access the trend of development of embalming technique that was developed after many trials and errors. In this paper, we have briefly discussed about the past, present and upcoming future technique of cadaver preservation with recent advances and modification. We also would like to recommend that new internationally recognized standard on embalming technique should be developed so that cadavers were excellently preserved and color remains natural.